ATTITUDES, OPINIONS, AND CHARACTERISTICS OF A SELECT GROUP OF ARKANSAS SPRING TURKEY HUNTERS - Michael E. Cartwright; Ronald A. Smith (Wildlife Society Bulletin)
Abstract: To improve research efforts and turkey (Meleagris gallopavo silvestris) hunting in Arkansas, we surveyed turkey hunters on their attitudes, opinions, preferences, and activities regarding spring turkey hunting. A questionnaire with 35 questions was mailed to all Arkansas National Wild Turkey Federation (NWTF) members (789) after the 1988 spring turkey season. Results characterized the average Arkansas NWTF member as male, 45 years of age, with a rural background and approximately 16 years of spring turkey hunting experience. The most important reasons for spring turkey hunting were associated with the outdoor environment and natural experiences. About half of the hunters thought that turkey numbers in the areas they hunted in the spring of 1988 were adequate but believed there were too many hunters. Hunters rejected proposed season changes that would reduce legal hunting opportunity, and >88% would not support mandatory hunter‐orange requirements. Highly favored proposals to improve spring turkey hunting included establishment of more walk‐in turkey hunting and wilderness areas, and closure of low population areas for stocking. Respondents perceived the greatest threats to spring turkey hunting were illegal harvest, unsafe hunters, poor hunter behavior, and free‐running dogs. Because respondents perceived legal and ethical problems as serious threats to spring turkey hunting, law enforcement and hunter education programs are important. Although NWTF members indicated some tolerance for program changes, tradition was still reflected in attitudes and opinions expressed. For this reason, a more aggressive information and education effort is warranted to achieve public support needed for a more progressive turkey management program in Arkansas.